The Impact of Project-Based Learning on Students’ Engagement in Learning Report Text - Shefaya, Fadiya Hayatis; Safriani, Afida; Kurniasari, Aulia Drifani (ICONELT, 2024)
ways. Nevertheless, no comprehensive studies examine how project-based learning affects student engagement, specifically in relation to the four areas of collaborative, strategic, responsible, and energized learning. Thus, this study examines how project-based learning affects students’ engagement in studying report text at SMAN 2 Sidoarjo, especially in grade 10, through a survey study. The Data was collected from 160 10th-grade students through questionnaires. According to the research, students showed a thorough comprehension of the objectives of their projects. They also expressed a sense of responsibility and pride in their work. Their desire to do well on their assignments was influenced by a number of things. This concludes with a suggestion for teachers who want to implement project-based learning in classroom learning. Teachers can consider the assignments they will be given by adapting to what is trending at that time. Therefore, students can be enthusiastic about completing projects because, when implementing project-based learning, learning activities are student-centered. For the future researcher who wants to do research about project-based learning the use of qualitative methods can be considered in order to investigate more deeply the impact of project based learning from the student’s perspective.